The Impact of Artificial Intelligence and Big Data on Managerial Decision-Making - Karimov , Abdusamat; Tursunov , Doniyorbek (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the growing significance of Artificial Intelligence and Big Data in reshaping managerial decision-making practices across organizations in both the public and private sectors. Rather than relying solely on traditional intuition-based approaches, modern management increasingly depends on intelligent systems capable of processing large volumes of data and generating actionable insights. The study focuses on how advanced analytical tools, including machine learning and predictive techniques, contribute to more informed, timely, and accurate decision outcomes. It also considers how organizations incorporate these digital technologies into their strategic frameworks, redefining conventional models of rational decision-making in a rapidly evolving technological environment. In addition, the research addresses the emerging ethical concerns and operational challenges linked to the implementation of AI-driven systems, such as data reliability, transparency, and accountability. The overall conclusion highlights that the integration of data-intensive analytics with intelligent technologies enables organizations to adopt evidence-based management approaches, increase efficiency, and strengthen governance through more transparent and accountable decision-making processes.